(untitled) (Research, Society and Development, 2021)
Recurrent aphthous stomatitis (RAS) is a more common disorder of the oral mucosa and is characterized by a well-defined, painful ulcerated lesion with a necrotic center, raised borders, and an erythematous halo. However, the characterization of a specific etiological agent for this condition has not yet occurred. RAS has three main forms, with the smallest RAS being the most common in the oral cavity, which are painful and well-defined ulcerations that heal within 10 to 14 days. Herpetiformis, which has several lesions and can coalesce between 7 and 10 days, finally we have the longest RAS, which can last for more than 6 weeks and can leave scars. Methodology: This study is a qualitative and descriptive case report, bringing relevant data from the literature. The ethical principles of the Declaration of Helsinki were respected and the patient signed the “Informed Consent Form” to participate in the research. The aim of this study was to report a case of RAS in a 41-year-old male patient with Sutton’s disease, presenting multiple necrotizing ulcers within 9 years of recurrence. Conclusion: As the etiology of RAS is still unknown and a common and recurrent disorder in the oral cavity, current treatment is diversified and focuses on relieving the symptoms of the disease, ranging from the use of natural products, topical use, anti-inflammatory drugs, immunomodulators and low power laser application.